Positive Predictive Value of Rapid Antigen Tests in School During SARS-CoV-2 Omicron Variant Surge. Issue 1 (18th October 2022) - Jang, Eun Jung; Choe, Young June; Yun, Go-Woon; Kim, Ryu Kyung; Jeong, Heegwon; Lee, Sangwon; Park, Young-Joon
Abstract : In Korea, we conducted a national observational study to calculate the positive predictive value of SARS-CoV-2 rapid antigen tests in K-12 schools during the Omicron variant surge in March 2022. The weekly positive predictive value ranged from 86.4% to 93.2%. The positive predictive value was the highest among elementary school students with symptoms (95.7%) and lowest among teachers/staff without symptoms (70.9%).